Comparison of registration status of Institutional Taska services in East Coast Malaysia - Kharuddin, Azrul Fazwan; Mustafa, Zaida; Azid, Norazura; Kharuddin, Darvinatasya; Ku Ibrahim, Ku Faridah; Hong, Lee Yoon; Syed Mohmad, Sharifah Omhani; Zahri, Zety Akhzar (Southeast Asia Early Childhood Journal, 2019)
The analytical comparative profile of the nursery services of TASKA in three states on the east coast of Malaysia namely Pahang, Kelantan and Terengganu is the main idea of this study. Survey method using questionnaire was conducted on 37 TASKA selected based on three registration status. The questionnaire was modified from the SERVQUAL Model. The data were analyzed using statistical chi-squared exact test. The findings show that there is no significant difference in the safety aspect shown by the institutional TASKA whether registered or unregistered. Nevertheless, the analysis shows that there is a significant difference in the nutritional aspect based on several items from the perspective of the caretaker. An independent sample t tests also found no significant difference between the registrationstatusesin all aspects. In conclusion, the difference in terms of the TASKA category can be assessed through different perspectives where safety and nutrition factors are the key indicators in this study.